TAMPANG JENUH TRANSFERIN PENDONOR DARAH ANEMIA - Christina Roosarjani; Titis Wahyuono; J B Suparyatmo (Indonesian Association of Clinical Pathologist and Medical laboratory, 2009)
Iron deficiency remains one of the most frequent adverse effects of blood donation. Iron status test used on blood donor screeningis haemoglobin concentration. Other iron status parameters are transferrin saturation. The study aims to determine the profile oftransferrin saturation among certain groups of blood donors at the Blood Transfusion Unit of the Indonesian Red Cross SurakartaBranch. The samples were drawn from blood donors at the Blood Transfusion Unit from June to December 2005. A total of 148 specimenswere classified into 3 groups consist of 49 first time blood donations as group I, 50 of fifth time blood donations as group II, and 49of tenth time blood donations as group III. Transferrin saturation was measured by ratio between serum iron and Total Iron BindingCapacity (TIBC). The data analysed by Anova test to distinguish the difference of transferrin saturation among three groups. The resultsshowed the transferrin saturation decreased from group I to group II and from group II to group III. The transferrin saturation amongthree groups showed significantly difference (p=0.000). It can be concluded that there is a decrease in transferrin saturation accordingto the blood donation frequency among blood donors at the Blood Transfusion Unit of the Indonesian Red Cross Surakarta Branch.Transferrin saturation measurement is needed for another parameter of iron deficiency anaemia among blood donors.